Analysis of new forms of orifice plates using computational fluid dynamics - Halas, Dragan; Bera, Oskar; Omorjan, Radovan; Rajic, Aleksandar; Jasin, Danijela (Hemijska industrija, 2019)
In many technologies, such as process industry or water supply, there is a need to measure fluid flowrates. Orifice plates are the most common instruments for measuring the fluid flowrate through pipelines due to their many advantages. On the other side, their use increases operating costs of industrial plants and pipelines. In this work, three new forms of orifice plates were designed and tested. These new forms and one standard, which served as a reference, were designed by using the SolidWorks software package. The aim of the new designs was energy savings, and consequently reduction of operating costs. Energy savings can be achieved by such a design, which decreases the orifice plate resistance an element of the pipeline. This was achieved by increasing the open part of the orifice plate permitting the fluid flow. CAD models of orifice plates were transferred to STL files that were further used for CFD simulation as well as 3D printing of experimental replicas. According to the proposed algorithm, the new designs were tested by CFD simulation performed in the COMSOL Multiphysics software package, by using a finite-difference method. Equations used were based on the Reynolds form of Navier-Stokes equations (RANS, Reynolds-averaged Navier-Stokes), and the continuity equation for incompressible fluids. Next, as we have proposed in our algorithm of development of new orifice plate designs, experimental orifice plates were made by using 3D printing technology and FDM (Fused Deposition Modeling) procedure and tested at laboratory conditions. The results of laboratory tests were compared with the results of CFD simulation. A considerable amount of energy saving was indicated, which was achieved already by the first of the three new orifice plate forms (V1) as compared to the reference (V0). For the other two proposed forms, the effect of energy savings was considerably lower. By using CFD simulation, data can be obtained based on which a decision can be made whether the new shape of the measuring device should be corrected or is appropriate for further laboratory tests. Based on the presented results it can be concluded that the proposed testing algorithm proved useful in designing new forms of orifice plates. nema